Investigation on Micro-structural Analysis of Fly Ash and Clay Compacts - Pattanaik, Ashutosh; Mishra, Subash Chandra; H., Adarsha (New Approaches in Engineering Research Vol. 11, 2021)
For its light weight, industrial waste such as fly-ash is commonly employed as a building material.The fundamental disadvantage of these bricks, however, is that they have a low compressive strength.As a result, there is a lot of research being done to improve the strength of these bricks. In order to keep costs down, ordinary clay is utilised to make bricks. As a result, research is being conducted to develop a new systematic technique for producing a new form of brick with higher compressive strength than standard clay bricks. Fly-ash is combined with clay in various compositions, sintered at various temperatures, and microstructural analysis is performed to identify a method to improve its properties.